1998
DOI: 10.1111/j.1349-7006.1998.tb00575.x
|View full text |Cite
|
Sign up to set email alerts
|

N‐Methyl‐N‐nitrosourea Concentration‐dependent, Rather than Total Intake‐dependent, Induction of Adenocarcinomas in the Glandular Stomach of BALB/c Mice

Abstract: The influence of the level of carcinogen exposure on histopathological types and cellular differentiation of the induced tumors was examined in 100 male BALB/c mice given N-methyl-Nnitrosourea (MNU) in their drinking water at 240 ppm on alternate weeks (total exposure: five weeks) (group 1), at 120 ppm similarly (total exposure: ten weeks) (group 2), at 60 ppm for 20 weeks continuously (group 3), or at 30 ppm for 40 weeks continuously (group 4). Forty-three differentiated and 17 undifferentiated type adenocarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 26 publications
1
44
1
Order By: Relevance
“…Thus milder treatment schedules were selected here. We earlier reported that the proportion of undifferentiated adenocarcinomas in the glandular stomach induced by MNU depends on the concentration of the carcinogen 22 and in this study, all adenocarcinomas were of well-differentiated type.…”
Section: Discussionsupporting
confidence: 67%
“…Thus milder treatment schedules were selected here. We earlier reported that the proportion of undifferentiated adenocarcinomas in the glandular stomach induced by MNU depends on the concentration of the carcinogen 22 and in this study, all adenocarcinomas were of well-differentiated type.…”
Section: Discussionsupporting
confidence: 67%
“…MNU (Sigma Chemical) was dissolved in distilled water at a concentration of 240 ppm and was freshly prepared twice per week for administration in drinking water in light-shielded bottles. The 6-week-old wild-type and Jnk1 À/À mice were given drinking water containing 240 ppm of MNU on alternate weeks for a total of 5 weeks of exposure, according to a protocol described in a previous report (19). The MNU-treated mice were sacrificed at 40 weeks after starting MNU administration.…”
Section: Methodsmentioning
confidence: 99%
“…Sixty-five PPARg (+/À) and 42 wild-type (+/+) mice, all male, age 4 to 7 weeks, were randomly divided into four groups, respectively. Animals in groups 2, 3, 6, and 7 were given drinking water containing 240 ppm MNU in light-shielded bottles on alternate weeks for a total of 10 weeks exposure, according to the protocol described in a previous report (37). Animals in groups 1, 4, 5, and 8 received only water.…”
Section: Methodsmentioning
confidence: 99%